2019
DOI: 10.1590/1676-0611-bn-2017-0333
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Meliponini and anothers Apiformes (Apidae sensu lato) in a Cerrado fragment and its surrounding, Campo Grande, MS

Abstract: The aim of this study was to evaluate the diversity of Meliponini and anothers Apiformes (Apidae sensu lato) from a Cerrado fragment and its surrounding. Malaise traps were installed in a pasture near a fragment of Cerrado and its surrounding, from October to December 2010. Samples were collected at seven-day intervals and preserved in Dietrich solution. The apiforms specimens from each sample were separated in morphospecies and sent to identification. The tribe Meliponini was the most abundant in open areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…The greatest representativeness of family Apidae regarding number of genera, species and individuals was also recorded by other studies performed in the Cerrado, Amazon Rainforest and in transition regions (Andena et al 2005, Santos et al 2004, Oliveira-Junior et al 2015, Lima & Silvestre 2017, Almeida et al 2019, Ferreira et al 2019). The tribe Meliponini was the most diverse and abundant group in the herein assessed biomes, and these data corroborate results recorded in other studies performed in Cerrado and transition sites (Almeida et al 2019, Santos et al 2004, Santiago et al 2009, Roel et al 2019). The highest abundance of species belonging to genus Trigona recorded in the present study was also observed in Cerrado-Amazon Rainforest transition sites assessed by Santos et al (2004), and in Cerrado areas assessed by D'avila &Marchini, (2008) andGianinni et al (2017).…”
Section: Richness and Abundancesupporting
confidence: 92%
See 2 more Smart Citations
“…The greatest representativeness of family Apidae regarding number of genera, species and individuals was also recorded by other studies performed in the Cerrado, Amazon Rainforest and in transition regions (Andena et al 2005, Santos et al 2004, Oliveira-Junior et al 2015, Lima & Silvestre 2017, Almeida et al 2019, Ferreira et al 2019). The tribe Meliponini was the most diverse and abundant group in the herein assessed biomes, and these data corroborate results recorded in other studies performed in Cerrado and transition sites (Almeida et al 2019, Santos et al 2004, Santiago et al 2009, Roel et al 2019). The highest abundance of species belonging to genus Trigona recorded in the present study was also observed in Cerrado-Amazon Rainforest transition sites assessed by Santos et al (2004), and in Cerrado areas assessed by D'avila &Marchini, (2008) andGianinni et al (2017).…”
Section: Richness and Abundancesupporting
confidence: 92%
“…There are several studies about bee communities in Cerrado showing a relatively large number of species in this Brazilian biome (Faria & Silveira 2011, Pires et al 2013, Lima & Silvestre 2017, Roel et al 2019). Nevertheless, with respect to Cerrado in Tocantins State, we only find the register of one study about bees' diversity in the state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A polinização direta de diversas culturas, promove melhorias qualitativas ou quantitativas na produção, o que faz com que certas plantações cheguem a ser 95% dependentes dos serviços ecossistêmicos providos por estes organismos. Uma vez que a maior parte das espécies ocorre naturalmente nos diferentes ecossistemas, a manutenção das áreas naturais ao redor da plantação traz um benefício adicional, que é o controle natural de pragas que atingem as culturas (Giannini et As abelhas que mais ocorrem no Cerrado são as Apinae, subfamília de abelhas nativas do Brasil (Roel et al 2019); dentro desta subfamília existe a tribo Meliponini, abelhas com hábitos sociais, ou seja, abelhas que constroem ninhos, na qual existem 417 espécies válidas descritas, sendo 33 gêneros exclusivamente neotropicais (Camargo & Pedro, 2013). Essas abelhas polinizam populações de plantas nativas e cultivadas que, muitas vezes, outras abelhas não conseguem ser tão eficientes (Giannini et al 2015), como no caso da castanheira-do-brasil (Bertholletia excelsa, Lecythidaceae), cuja polinização exige que a abelha levante o capuz da flor para acessar o néctar (Cavalcante et al 2012).…”
Section: Partamona Cupiraunclassified